Synthèse d’entretien avec un initié de la société Bobo - Traoré, Seydou; Sanon, Boukary (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This summary was written following an interview with a Bobo insider in Bobo Dioulasso. These exchanges concerned the types of faults encountered among the Bobo, the actors of Bobo customary justice, as well as the process of crime management among the Bobo. Discussions also focused on the meaning of community mediation, popular perceptions of modern and customary justice, and popular perceptions of prisons as a model of punishment for children.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Bobo (African people); Community Insider